Kemerosotan Ekonomi Negara Sebagai Dampak Pembatasan Sosial Covid 19 di Indonesia - Annissa Rezki; Nur Rohim Yunus (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
The case of Corona Covid-19 is now in its second year. The impacts that occur are very numerous and greatly affect every level of society from all sides and aspects of life. The many impacts and changes that occur during the pandemic are not easy and can be accepted by the community. The many pros and cons as well as issues that lead to public opinion on the emergence of the Covid-19 case also make the condition of the country more difficult. The imposition of restrictions that are always extended and the difficulty of accessing public transportation until there is a reduction in employees not only adds to the number of cases of poverty in Indonesia but also adds to the increasing number of criminal cases caused by difficult economic conditions. In this paper, the author tries to describe and provide views on the journey of covid-19 into Indonesia and what impacts it has during this covid-19 pandemic.Keywords: Corona Covid-19; Social distancing; Impact of Covid AbstrakKasus Corona Covid-19 kini sudah memasuki tahun kedua. Dampak yang terjadi sangat banyak dan sangat mempengaruhi setiap lapisan masyarakat dari segala sisi dan aspek kehidupan. Banyaknya dampak dan perubahan yang terjadi selama pandemi tidak mudah dan dapat diterima oleh masyarakat. Banyaknya pro kontra serta isu yang memunculkan opini publik terhadap munculnya kasus Covid-19 juga membuat kondisi negara semakin sulit. Pemberlakuan pembatasan yang selalu diperpanjang dan sulitnya akses transportasi umum hingga terjadi pengurangan pegawai tidak hanya menambah jumlah kasus kemiskinan di Indonesia, tetapi juga menambah jumlah kasus kriminal yang disebabkan oleh kondisi ekonomi yang sulit. Dalam tulisan ini, penulis mencoba mendeskripsikan dan memberikan pandangan tentang perjalanan covid-19 masuk ke Indonesia dan apa dampaknya selama pandemi covid-19 ini.Kata Kunci: Corona Covid-19; Jarak sosial; Dampak Covid